(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the present time, machine learning algorithms are used for design concreate strength prediction models due to numerous advantages over the manual methods such as cost and time effective and more effectively predict the strength based on the historical information. Therefore, the main aim of this paper, is to study and analyse the various machine learning algorithms are used to design concrete strength prediction model. In the literature, last five years paper is taken under consideration. Based on literature survey, open research gaps are defined which helps the other authors to contribute their research in this area.